PENGEMBANGAN MEDIA PAKAN ULAT PADA PEMBELAJARAN MATEMATIKA MATERI PEMBAGIAN BILANGAN 2 ANGKA UNTUK SISWA KELAS IV SDN TIRON 4 - Anggun Dwi Oktaviani; Kharisma Eka Putri; Alfi Laila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop innovative learning media in the form of FEED OF CATTLE (Snakes and Ladders Bag Board) on the material of dividing two-digit numbers for fourth-grade students of SDN Tiron 4. The background of this study is the low interest and learning outcomes of students and the use of learning media that are less interesting. The method used is Research and Development (R&D) with the ADDIE development model which includes the stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were 24 students and 1 homeroom teacher. Data collection techniques in the study were validity (media and material expert questionnaires), practicality (teacher and student response questionnaires), and effectiveness (post-test). The results of the validation data showed that the FEED OF CATTLE media met the criteria of Very Valid with a media validation score of 86% and material validation of 95%. The practicality of the media based on the teacher response questionnaire obtained a score of 98%, included in the Very Practical category. The effectiveness test showed that 94% of students achieved learning mastery with a post-test score above the KKM, included in the Very Effective category. Based on these findings, it can be concluded that the FEED CATTLE learning media is valid, practical, and effective for use in mathematics learning, particularly in the division of 2-digit numbers. This media can be an alternative solution to improve the understanding and learning outcomes of elementary school students.